Plzz answer Question no. 5 As given in image
Attachments:
![](https://hi-static.z-dn.net/files/d26/b052e9316a4886b8870e7f6ddd38789b.png)
Answers
Answered by
1
Answer:
If p and q are the roots of the equation x2 +bx+c then:
p+q=(-b)/a = -(-(k+6))/1
p*q=c/a = 2(2k-1)/1
According to the information: p+q=1/2(p*q)
k+6=(1/2) *(2*( 2k-1))
solve it and see that it comes to.....
k+5=2k-1 [subtract both sides by k]
5=k-1
k=5
SOLVED,
HOPE YOU UNDERSTOOD,GOOD LUCK!!!
Answered by
2
HOPE ITS HELPFUL.....:-)
Attachments:
![](https://hi-static.z-dn.net/files/ddf/772d64f5908acfba98cb4d629feddbe5.jpg)
Similar questions